Symmetry of propulsion exerted during tethered- and free-swimming - Fantozzi, S.; Fantozzi, S.; Russo, G.; Coloretti, V.; Cortesi, M. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Swimming is characterized by body propulsion, where the upper limbs are the main contributor (Zamparo et al., 2020). To investigate the improvement of propulsion, numerical and experimental methods were applied (Santos et al., 2021). While the numerical approaches can help in visualizing and understanding the complex hydrodynamic mechanism, the experimental one (e.g., tethered swimming and wearable pressure sensors) can allow the "inpool" assessment with strong ecological validity thanks to the recent technology developments in pressure sensors (i.e., eliminating cables and reducing the encumbrance to the swimmer in terms of fixing the device to the body). Propelling measurement during tethered swimming was proposed as an alternative tool of free swimming due to difficulties in quantifying it during free swimming and considered analogous in terms of swimming technique. However, due to the stationary nature and the propulsion more overlapping between arms in the tethered test, differences between the two conditions were highlighted (Morouço et al., 2011; Samson et al., 2019). Furthermore, in the last two decades, the balance between dominant and non-dominant arms was considered a key factor in investigating the propulsion mechanism of the swimmer, as it may significantly impact swimming performance (Psycharakis et al., 2021; Sanders et al., 2015). Thus, the aim of the present study was to analyze the propelling forces of the two hands during free (Free) and tethered (Tet) swimming conditions using wearable pressure sensors. A comparison between dominant and non-dominant arms was also investigated.